The raven and the intermediality - Vitoriano, Helciclever Barros da Silva (2015)
Translation by Lenice Medeiros, PhD and translator. An initial and expanded version of this text was published in french in another scientific journal, “Cadernos de Tradução”, available at: https://periodicos. ufsc.br/index.php/traducao/article/view/2175-7968.2015v35n2p41/30992. Access: 1 Mar. 2016.